Cardiovascular response to postural perturbations of different intensities in healthy young adults. Issue 9 (9th May 2022) - Siedlecki, Patrick; Shoemaker, J. Kevin; Ivanova, Tanya D.; Garland, S. Jayne
Abstract: The ability to regain control of balance is vital in limiting falls and injuries. Little is known regarding how the autonomic nervous system responds during recovery from balance perturbations of different intensities. The purpose of this study was to examine the cardiovascular response following a standing balance perturbation of varying intensities, quantify cardiac baroreflex sensitivity (cBRS) during standing perturbations, and to establish the stability of the cardiac baroreflex during quiet standing before and after balance disturbances. Twenty healthy participants experienced three different perturbation intensity conditions that each included 25 brief posteriorly‐directed perturbations, 8–10 s apart. Three perturbation intensity conditions (low, medium, high) were given in random order. Physiological data were collected in quiet stance for 5 min before testing (Baseline) and again after the perturbation conditions (Recovery) to examine baroreflex stability. Beat‐to‐beat heart rate (HR) and systolic blood pressure (SBP) analysis post‐perturbation indicated an immediate acceleration of the HR for 1–2 s, with elevated SBP 4–5 s post‐perturbation. Heart rate changes were greatest in the medium ( p = 0.035) and high ( p = 0.012) intensities compared to low, while there were no intensity‐dependent changes in SBP. The cBRS was not intensity‐dependent ( p = 0.402) but when perturbation conditions were combined, cBRS was elevated compared to Baseline ( p = 0.046). The stability of baseline cBRS was excellent (ICC = 0.896) between quiet standing conditions. In summary, HR, but not SBP or cBRS were intensity‐specific during postural perturbations. This was the first study to examine cardiovascular response and cBRS to postural perturbations. Abstract : We examined the cardiovascular response following a standing balance perturbation of varying intensities, and quantified cardiac baroreflex sensitivity during standing perturbations. Beat‐to‐beat heart rate and systolic blood pressure analysis found an immediate acceleration of the heart rate, with elevated blood pressure lagging. The cardiac baroreflex sensitivity was not intensity‐dependent.